ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PROYEK PEMBANGUNAN GUDANG LOGISTIK POLRES LAMONGAN - Mayasari, Intan; Zamaniah, Zamaniah; Masvika, Hendra; Permatasari, Citra; Ramadhon, Ardiana; Wardani, Agustina (Jurnal Teknik Sipil Giratory UPGRIS, 2026)
The construction of the Lamongan Police Logistics Warehouse, as part of public infrastructure, requires efficient supervision to support police operational needs. However, several operational issues have arisen, hindering timely completion. One of the main problems is delays in material delivery, which significantly disrupt project progress. This study aims to analyze the factors influencing delays in the warehouse construction project, focusing on the roles of contractors, suppliers, consultants, and project owners. Using a quantitative approach, the research identifies both internal and external factors that contribute to construction delays. Multiple linear regression analysis was employed to examine the relationship between independent variables (work environment, material delays, equipment, labor, and design changes) and project implementation delays. The findings indicate that labor is the most influential factor, with a beta value of 0.455, followed by design changes, which have a positive though relatively minor effect. In contrast, work environment, material delays, and equipment factors show no significant impact. To mitigate delays, the study recommends strengthening coordination among stakeholders, improving resource management, and enhancing project planning. The research provides valuable insights for improving construction project management and preventing unforeseen delays in similar future projects.